The Cyanation of Prochiral Aldehydes with Chiral Copper Complexes of R-(+)/S-(-) -α-Ethylphenyl Amine in Methanol - Mei, Luo (Current Organic Synthesis, 2016)
Interesting and unexpected results on the cyanation of prochiral aldehydes catalyzed by chiral copper complexes of R-(+)/(S)-(-) α-ethylphenyl amine (I/II) in anhydrous methanol are presented. The cyanation reaction with chiral copper complexes of R-(+)/S-(-) α-ethylphenyl amines, acetols in methanol perform to afford a series of chiral products such as amines and acetonitriles (compounds 4-6, 8, 10 and 11). The obtained products are fully characterized by NMR, IR and X-ray analysis. The proposed mechanism for the formation of a series of chiral products can be concluded that methanol firstly promotes the decomposition of the copper complexes bearing R- (+)/S-(-) α-ethylphenyl amines to the ligand R-(+)/ S-(-)-α-ethylphenyl amine, which then conjugated with the initial TMS ether of the cyanohydrin or cyanohydrin to afford the chiral compounds 4-6, 8, 10 and 11.
Keywords: Cyanation